Tailoring the Magnetic and Electrical Properties of Epoxy Composites Containing Olive-Derived Biochar through Iron Modification - Erik Piatti; Daniele Torsello; Gaia Gavello; Gianluca Ghigo; Roberto Gerbaldo; Mattia Bartoli; Donatella Duraccio (Nanomaterials, 2023)
The combination of conductive carbon together with magnetic particles is a consolidated strategy to produce cutting-edge fillers for the production of polymer composites able to shield against microwave radiation. In this work, we developed and characterized an iron-tailored biochar obtained from the pyrolysis of olive pruning which was added as filler for the preparation of epoxy composites. The biochar-based composites were obtained by keeping the filler concentration at 10 and 40 wt.%. An extensive characterization was carried out in order to assess the electrical and magnetic properties of the composites containing biochar and iron-tailored biochar. The highest DC electrical conductivity of 59 mS/m was observed in the 40 wt.% iron-tailored biochar-loaded composite, while the reduction of the filler loading led to a drastic reduction in conductivity: 60 μS/m in the 10 wt.%-loaded composite. Ferromagnetic behavior of composites containing iron-tailored biochar is visible in the emerging hysteretic behavior, with a magnetic signal increasing with the filler concentration. Finally, both the complex permittivity (ε’) and the AC conductivity (σ) are enhanced by increasing the BC filler amount in the matrix, regardless of the presence of iron.